Isolasi Dan Karakterisasi Bakteri Termo-Proteolitik Sumber Air Panas Sungai Medang, Sungai Penuh, Jambi - Dina Wahyuna; Anthoni Agustien; - Periadnadi (Universitas Andalas, 2012)
A study on isolation and characterization of thermoproteolytic bacteria from hot springs at Sungai Medang, Sungai Penuh, Jambi was conducted from March to June 2012 using a descriptive method. Seventy thermophylic bacteria were isolated from the hot springs. A Total of 39 thermoproteolytic bacteria 39 were identified. The highest enzymatic activity (13.59 U/ml) was shown by isolate MI2.3 from a location at which the temperature was 600C. The isolate MI2.3 was characterized as an aerobic thermoalkaliphylic (optimum temperature of 500C, optimum pH of 9.0) bacterium with the ability to produce amylase but neither lipase nor cellulase.Keywords : alkaliphylic, bacterium, enzymatic activity, proteolytic, thermophylic.